2014
DOI: 10.1155/2014/501434
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation of a Light-Gas Gun Facility for Impact Test

Abstract: Experimental tests which match the application conditions might be used to properly evaluate materials for specific applications. High velocity impacts can be simulated using light-gas gun facilities, which come in different types and complexities. In this work different setups for a one-stage light-gas gun facility have been numerically analyzed in order to evaluate their suitability for testing materials and composites used as armor protection. A maximal barrel length of 6 m and a maximal reservoir pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…To ensure safe operations, understanding the properties of materials subjected to impact conditions is critical in various aerospace applications. To address this issue, specific tools are necessary to assess the impact damage on structures and systems [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure safe operations, understanding the properties of materials subjected to impact conditions is critical in various aerospace applications. To address this issue, specific tools are necessary to assess the impact damage on structures and systems [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the projectile muzzle velocity was lower with the real gas model compared with velocities calculated using the ideal gas model, and the error between the two models gradually increased as the distance travelled by the projectile inside the launch tube increased. Furthermore, Rahner et al (2014) conducted a numerical evaluation of the gas gun using Seigel's proposed model, to determine the most efficient gas gun for different purposes. Their paper focused on the limits and tradeoffs to be considered when designing the gas gun.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the projectile muzzle velocity was lower with the real gas model compared with velocities calculated using the ideal gas model, and the error between the two models gradually increased as the distance travelled by the projectile inside the launch tube increased. Furthermore, Rahner et al conducted a numerical evaluation of the gas gun using Seigel's proposed model, to determine the most efficient gas gun for different purposes [3]. Their paper focused on the limits and tradeoffs to be considered when designing the gas gun.…”
Section: Introductionmentioning
confidence: 99%